The Impact of Production Factor and Costs on Business Income of Red Onion Farming Business as an Icon of Fried Red Onion Production in Sigi District, Central Sulawesi - Armin Muis; Muhtar Lutfi; Eko Jokolelono; Nurnaningsih Nurnaningsih; Ika Rafika; Nuryana Dj Haprin (Agro Ekonomi, 2023)
This study aims to determine and analyze direct correlation of capital, man power, land size, and also production costs to income of red onion farming business; the impact of capital, man power, and also land size towards cost of red onion farming business; and the impact of capital, man power, land area towards income through the cost of red onion farming business in Sigi District. This research used primary data. Population was red onion farmer from three villages and the sample was deliberately determined considering that three villages are red onion producing areas in this district. Analysis for this research are using a structural equation model. From the analysis showed: (1) Production factors of capital, man power and land size had a direct and influential impact towards income; (2) Concerning the impact from production factor on costs, the capital variable had a positive and influential impact towards costs; man power variable had a positive and influential impact towards costs, and  land size had a positive and influential impact towards costs; (3) In terms of indirect impact, the variables of capital, man power and land size have a positive and influential impact towards income through mediation of red onion farming costs at Sigi District, Central Sulawesi, Indonesia.